Choosing the Right Type and Location of the City Public Transport Stops - Ivana Olivkova (Communications - Scientific letters of the University of Zilina, 2006)
This paper is concerned to tram stop safety in the Czech Republic. Recently some experimental solutions of tram stops (with alternative successes) have been realized in Prague and Brno. These experimental solutions of tram stops, which very often emerged as trial and error, were based on elevated carriageways. Due to the fact that there is lack of qualified information and projection recommendations, I would like to present the selection of information based on real operation experience. The paper has been compiled using results of the grant project No. 103/04/0476 “Proposal of financing traffic attendance methodology”, which is being realised thanks to the financial support from the public Grant Agency of the Czech Republic [1].